Projecting the future smoking prevalence in Norway - Gartner, Coral E.; Lund, Karl E.; Barendregt, Jan J.; Mohamed Nor, Norashidah; Hassan, Heidy; Vedøy, Tord F.; Kvaavik, Elisabeth (Oxford University Press, 2016)
Background: Norway has achieved a noteworthy reduction in smoking prevalence over the past forty years. In 2015, 13% of Norwegians aged 13–74 smoked daily and a further 9% smoked occasionally. One of the objectives of the Norwegian 2013–16 national strategy for tobacco control is to achieve a reduction in the daily smoking prevalence to < 10% by 2016. This paper aims to estimate how long it will take for Norway to achieve the 10% smoking prevalence. Methods: A dynamic forecasting model using smoking prevalence data from national survey data on the prevalence of current, former and never smokers in the Norwegian population from 1985 to 2012 was used to estimate future smoking prevalence in the Norwegian population based on a continuation of current patterns in smoking cessation and initiation rates. Results: The result suggests that Norway’s smoking prevalence among men and women will continue to decline if current trends of smoking initiation and cessation continue. Our model predicts, based on figures for 1985–2012, that the prevalence of current daily and occasional smoking among men and women will not fall below the 10% mark until 2029 for men and 2026 for women, if current trends continue. Conclusion: Smoking is likely to remain an important public health issue in Norway for many years. New strategies are needed to accelerate the decline in smoking in Norway.